Analisis Strategi Pengembangan Infrastruktur Dan Konektivitas Maritim Indonesia - Aji, Muhammad Sajidin; Heppi, Heppi Nurani Limbong Litak; Fatmawati, Fatmawati Cahya Ningrum (Jurnal Ilmu Hubungan Internasional LINO, 2024)
The purpose of this study is to analyze Indonesia's maritime infrastructure and connectivity development strategy. The focus of this research is on strategies and policies related to infrastructure development and connectivity in accelerating the realization of Indonesia's vision as the world's maritime axis, as the flagship program of President Jokowi's government by optimizing blue ecomony or by optimizing maritime potential to improve the welfare of the Indonesian people. The research method used in this study is qualitative with data collection from various sources such as books, journals, research reports and official documents. The results show that during President Joko Widodo's leadership, namely from 2014-2024, there has been significant progress in the development of Indonesia's maritime infrastructure and connectivity such as port construction, sea toll networks, and other related infrastructure. However, in infrastructure development and connectivity, there is still a lack of infrastructure in some regions, there is an imbalance in cargo flows between regions and limited funding in optimizing maritime potential. Periodic evaluations and synergies between the government, private sector, and community are needed to address these challenges and support inclusive and sustainable economic growth in Indonesia as a maritime nation